Peningkatan Kapasitas Masyarakat dalam Mitigasi Banjir Melalui Pelatihan dan Penerapan Rumah Amfibi di Wilayah Rawan Bencana Kalimantan Tengah - Dhimas Ari Yudha Pratama; Mochammad Fabian Athaya; Aurora Maria Sagak Abel; Thea Farina; Nuraliah Ali; Satriya Nugraha (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study examines community capacity building for flood mitigation in flood-prone regions of Central Kalimantan through disaster education, technical training, and the construction of an amphibious house prototype. Using a community-based disaster risk reduction (CBDRR) framework, the program integrates participatory training, field surveys, and adaptive structural innovation. Findings indicate a 40% increase in community knowledge based on Community Empowerment Level Analysis results, active engagement of 35 participants in disaster education, and significant improvement in technical skills among 22 trainees involved in amphibious foundation construction. The prototype achieved 100% completion within four effective working days, demonstrating the feasibility of amphibious technology using locally available materials. Strengthening youth organization structures further enhances community readiness and institutional resilience. Overall, the integration of participatory learning and adaptive technology effectively builds community self-efficacy and disaster preparedness in flood-prone environments.